Drinfeld J Presentation of Twisted Yangians - Belliard, S.; Regelskis, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We present a quantization of a Lie coideal structure for twisted half-loop algebras of finite-dimensional simple complex Lie algebras. We obtain algebra closure relations of twisted Yangians in Drinfeld J presentation for all symmetric pairs of simple Lie algebras and for simple twisted even half-loop Lie algebras. We provide the explicit form of the closure relations for twisted Yangians in Drinfeld J presentation for the sl3 Lie algebra.